Double ionization of helium by proton impact: from intermediate to high momentum transfer - Ambrosio, Marcelo José (2017)
We study theoretically the double ionization of helium by 6 MeV proton impact. For suchfast projectiles, when considering the projectile-target interaction to first order, the four-body Schr¨odingerequation reduces to solving a three-body driven equation.We solve it with a generalized Sturmian functionsapproach and, without evaluating a transition matrix element, we extract the transition amplitude directlyfrom the asymptotic limit of the first order scattering solution. Fivefold differential cross sections (FDCS)are calculated for the double ionization process for a number of coplanar kinematical situations. We presenta detailed theory-experiment comparison for intermediate momentum transfers (from 0.8 to 1.2 a.u. andfrom 1.4 to 2.0 a.u.). In spite of some experimental restrictions (energy and momentum ranges) and thelow count rates, we found that our theoretical description provides a very satisfactory reproduction ofthe measured data on relative scale. We then explore how the binary, recoil and back-to-back structureschange with increasing momentum transfers (0.853 to 1.656, to 3.0 a.u.). Within the impulsive regime,with a momentum transfer of 3.0 a.u., we also analyze the FDCS for different excess energies. Finally, inanalogy to an experimentalist gathering electrons with different excess energies to obtain enough counts,we provide a collective FDCS prediction that hopefully will stimulate further measurements.